Association of Serum Albumin, Globulin, and Transferrin Levels in Children of Poorly Managed Celiac Disease. (1st February 2023) - Siddiqui, Komal; Uqaili, Arsalan Ahmed; Memon, Salma; Shah, Tazeen; Shaikh, Saima Naz; Memon, Ali Raza
Abstract : Background . Celiac disease (CD) is an autoimmune genetic disorder in which gluten protein causes inflammation of the intestinal enterocytes. CD diagnosis in most cases is delayed or mistreated due to its varied clinical features. We aimed to evaluate the protein profile imbalance in different CD groups of children, which could help aid in the diagnosis and proper management of the disease. Methodology . This was a cross-sectional study with a nonrandom purposive sampling technique. All samples were taken from tertiary care hospitals of Hyderabad, Pakistan. In total, there were 175 children (age 3-15 years) divided into five equal groups (n = 35 ), namely, group A (control), group B (celiac diagnosed), group C (celiac-like symptoms), group D (celiac with type 1 diabetes mellitus), and group E (type 1 diabetes mellitus only). Clinical symptoms and laboratory parameters were analyzed among all the groups. Sera proteins, albumin, globulins, and transferrin levels were evaluated and compared with healthy individuals. Results . The albumin in serum of celiac groups B and C was 3.0 g/dl and 2.8 g/dl, respectively. While in diabetic patients with CD, it is 2.7 g/dl. The globulin levels were raised among all the celiac groups with typical GIT symptoms. The highest transferrin was observed in group B, celiac patients with severe anemia. Patients were not on GFD, hence had no or less recovery and had chronic symptoms of celiac. Conclusion . The misdiagnosis and poor management of celiac leads to chronic villous atrophy with imbalance in metabolic profile. Serum analysis of albumin, globulins, and transferrin may help in the diagnosis and proper management of the disease to recover the celiac symptoms.